The Emotional Empathy and its Relation to the Aesthetic Response among Students of the Fine Arts College - Jeyran Sabah Abdulla; Twana Yahya Khudhur (Zanco Journal of Human Sciences, 2025)
Research Objectives: The current research aims to identify: - The current research aims to investigate the following:- The level of emotional empathy among students of the College of Fine Arts. -The level of aesthetic response among students of the College of Fine Arts. -The relationship between emotional empathy and aesthetic response among students of the College of Fine Arts. -The significance of statistical differences in emotional empathy and aesthetic response among students of the College of Fine Arts based on gender (male-female) and academic stage (first year - second year - third year - fourth year). The research community consists of students from the College of Fine Arts at Salahaddin University/ Erbil, totaling 324 students. The researchers selected a sample of 200 individuals randomly from the College of Fine Arts. The researchers utilized two tools in their study: the first tool to measure emotional empathy (Al-Aasimi, 2015), and the second to measure aesthetic response (Hassan & Abdulhameed, 2023). The results obtained by the researchers are as follows: -High levels of emotional empathy were found among the research sample. -High levels of aesthetic response were found among the research sample. -There is a significant positive correlation between emotional empathy and aesthetic response. -There are statistically significant differences in emotional empathy based on gender among students, favoring females. -There are no statistically significant differences in aesthetic response based on gender. -There are no statistically significant differences in emotional empathy and aesthetic response based on academic stage among students of the College of Fine Arts.